2007
DOI: 10.1021/pr070112q
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Analysis of Nonenzymatically Glycated Peptides:  Boronate Affinity Chromatography Coupled with Electron-Transfer Dissociation Mass Spectrometry

Abstract: Non-enzymatic glycation of peptides and proteins by D-glucose has important implications in the pathogenesis of diabetes mellitus, particularly in the development of diabetic complications. However, no effective high-throughput methods exist for identifying proteins containing this low abundance post-translational modification in bottom-up proteomic studies. In this report, phenylboronate affinity chromatography was used in a two-step enrichment scheme to selectively isolate first glycated proteins and then gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 34 publications
4
154
0
1
Order By: Relevance
“…We also demonstrated that, compared to dual enrichment on both protein and peptide levels, affinity enrichment on the peptide level is more applicable when a limited amount of sample is available. 20 Further, glycated species were observed to be present in only bound fractions, which reduced the number of samples requiring LC-MS/MS analysis. 20 Therefore, because of the limited amount of sample (∼500 μg of total protein obtained) in the current study, erythrocyte membranes and the low-abundance portion of plasma proteins (∼4% of whole plasma protein weight) were affinity-enriched at only the peptide level ( Figure 1).…”
Section: Bac Enrichment Of Glycated Peptidesmentioning
confidence: 98%
See 2 more Smart Citations
“…We also demonstrated that, compared to dual enrichment on both protein and peptide levels, affinity enrichment on the peptide level is more applicable when a limited amount of sample is available. 20 Further, glycated species were observed to be present in only bound fractions, which reduced the number of samples requiring LC-MS/MS analysis. 20 Therefore, because of the limited amount of sample (∼500 μg of total protein obtained) in the current study, erythrocyte membranes and the low-abundance portion of plasma proteins (∼4% of whole plasma protein weight) were affinity-enriched at only the peptide level ( Figure 1).…”
Section: Bac Enrichment Of Glycated Peptidesmentioning
confidence: 98%
“…20 Further, glycated species were observed to be present in only bound fractions, which reduced the number of samples requiring LC-MS/MS analysis. 20 Therefore, because of the limited amount of sample (∼500 μg of total protein obtained) in the current study, erythrocyte membranes and the low-abundance portion of plasma proteins (∼4% of whole plasma protein weight) were affinity-enriched at only the peptide level ( Figure 1). Alternatively, whole plasma proteins were processed using dual enrichment, first at the protein level and then at the peptide level.…”
Section: Bac Enrichment Of Glycated Peptidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Another issue for the bottom-up approach by traditional peptide mapping is the varying degree of neutral water loss on the sugar with collision induced dissociation (CID) observed through tandem mass spectrometry (MS/MS) analysis of glycated peptides, which makes low-level detection of glycation sites even more challenging. [52][53][54][55] An alternative way of fragmentation in mass spectrometry is the electron transfer dissociation (ETD). Studies on the fragmentation method comparison show ETD provides complete sequence fragmentation without any neutral loss.…”
Section: Charge-based Methodsmentioning
confidence: 99%
“…However, the sensitivity of low abundance protein or peptide for ETD is low because of the low fragmentation efficiency. 53,54,[56][57][58] These issues often require extra experiments to confirm or detect glycated peptides. 31 Another way of improving the sensitivity and reducing the neutral loss of the glycated peptide is by using sodium borohydride or sodium cyanoborohydride reduction followed by trypsin cleavage and peptide map analysis with MS/MS detection.…”
Section: Charge-based Methodsmentioning
confidence: 99%